Adhesive Removal Procedures in Orthodontics: A Literature Review - Anjusha Divakar; Ravindra Kumar Jain (Journal of Clinical and Diagnostic Research)
The removal of residual adhesive after orthodontic bracket debonding is a critical step in restoring enamel surface integrity while minimising damage. Over the years, multiple techniques have been developed to remove orthodontic adhesive, including mechanical, chemical, and laser-based methods. While current methods are effective in removing adhesive residues, many are associated with enamel surface damage, time inefficiency, or patient discomfort. Given the widespread use of adhesive removal instruments by orthodontists, it is essential to have scientific knowledge about these techniques and their biological impact on tooth structure. Consequently, it is crucial to select effective removal methods that minimise damage to the patient at the end of treatment and, whenever possible, preserve the tooth’s original condition. Most authors prefer using a combination of abrasives and rotary speeds for effective appliance debonding, although the optimal choice of abrasive and speed remains unclear. Tungsten carbide burs receive the most favourable reviews in the literature, making them the recommended technique. Although the laser is more comfortable due to the lack of noise, vibration, or pressure, it creates a much rougher surface and is less effective compared to conventional methods. The present review aimed to summarise the available evidence on adhesive removal techniques reported in the literature and discuss their effects on the enamel surface and its integrity post-orthodontic treatment.